2021
DOI: 10.4236/jacen.2021.101009
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tef (<i>Eragrostis tef</i> (Zucc.) Trotter) to Balanced Fertilizer in Wolaita Zone, Southern Ethiopia

Abstract: Tef is grown as an important domestic cereal in Ethiopia. Currently, global attention is given for it particularly as a "health food" due to the absence of gluten and gluten like proteins in its grains. Regardless of its wider adaptation, productivity of tef is low in the country with the national average grain yield of 1.379 tons•ha −1. This is mainly because of low soil fertility and severe organic matter depletion intensified by low rate of chemical fertilizer application. This study was conducted to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The improvements in 1000 seed weight due to N application rate might be the increase in chlorophyll concentration which led to a higher photosynthetic rate for grain development and then, reduce with further application of N rate (Table 3). In line with this result, Ekero et al (2021) found that the weight of 1000-grains was maximum when nitrogen was applied at a rate of 40 kg ha −1 in teff. Similarly, Anjum et al (2015) reported that the application of maximum N rate increased the 1000 seed weight in Mung bean.…”
Section: Thousand Seed Weightsupporting
confidence: 68%
See 3 more Smart Citations
“…The improvements in 1000 seed weight due to N application rate might be the increase in chlorophyll concentration which led to a higher photosynthetic rate for grain development and then, reduce with further application of N rate (Table 3). In line with this result, Ekero et al (2021) found that the weight of 1000-grains was maximum when nitrogen was applied at a rate of 40 kg ha −1 in teff. Similarly, Anjum et al (2015) reported that the application of maximum N rate increased the 1000 seed weight in Mung bean.…”
Section: Thousand Seed Weightsupporting
confidence: 68%
“…This might be obtained due to the more availability of N that might have played a vital role in facilitating the growth and development of plants through cell division. Consistent with these results, Ekero et al, 2021;Fenta, 2018;Wato, 2019 reported a significantly maximum number of tillers in response to the application of a high N rate in tef. Likewise, Okubay et al (2014) reported that the number of fertile tillers per plant increased linearly with an increasing rate of applied SRU from 9 in the plots without N (control) to 22.67 in the plots supplied with 69 kg N ha −1 .…”
Section: Number Of Fertile Tillerssupporting
confidence: 58%
See 2 more Smart Citations
“…Tef is very sensitive to lodging because of high soil N or high external N application. Generally, tef harvest index is lower than other small grain cereals (Ekero et al 2021). The optimal N rates for tef production in SM4, M3, SH3 and SM3 were found to be 69, 92, 46 and 46 kg N ha −1 (Table 3).…”
Section: Discussionmentioning
confidence: 93%